Niosomes as Efficient Nanocarriers for Targeted Drug Delivery (Asian Journal of Pharmaceutics (AJP), 2024)
The localization of pharmacological molecules to stick locations is made possible by target-specific drug deliverysystems with its bi-layer structure made of non-ionic surfactants, the noisome vesicular system can temporarilyincrease a drug’s bioavailability in a specific location. Scientists who study drug delivery systems have been highlyconcerned with the creation of vesicles as a means of enhancing medication delivery in recent years. Niosomes’amphiphilic character enhances their ability to effectively encapsulate hydrophilic or lipophilic medications. Itis common practice to add additional ingredients, like cholesterol, to preserve the niosomes’ structural stiffness.When comparing the great chemical stability and effectiveness of the replacement with niosomes, liposomes usevesicles for medicinal and therapeutic applications, which have several advantages. They boost the therapeuticefficiency of drug molecules by keeping the medicine from exiting circulation too quickly, shielding it from itsgenetic environment, and lessening its effect on target cells. This research concentrated on current advancementsin the distribution of niosomal medications, potential advantages over other delivery systems, building techniques,characterization techniques, and recent research that is noisy. The use of niosomes in nanotechnology has thepotential to yield highly targeted, non- infective, and non-cancer agents. Proniosomes and aspasomes are a fewexamples of novel concepts that have been used to enhance niosomes’ drug delivery capabilities. Niosomesare also beneficial as a living component of vaccines and for diagnostic tests. Therefore, further research anddevelopment are required in these areas to produce the niosomal preparations that are now on the market.